Why is `f <$> g <$> x`

equivalent to `(f . g) <$> x`

although `<$>`

is not right-associative?

(This kind of equivalence is valid in a popular idiom with plain `$`

, but currently `$`

is right-associative!)

`<*>`

has the same associativity and precedence as `<$>`

, but behaves differently!

Example:

```
Prelude Control.Applicative> (show . show) <$> Just 3
Just "\"3\""
Prelude Control.Applicative> show <$> show <$> Just 3
Just "\"3\""
Prelude Control.Applicative> pure show <*> pure show <*> Just 3
<interactive>:12:6:
Couldn't match type `[Char]' with `a0 -> b0'
Expected type: (a1 -> String) -> a0 -> b0
Actual type: (a1 -> String) -> String
In the first argument of `pure', namely `show'
In the first argument of `(<*>)', namely `pure show'
In the first argument of `(<*>)', namely `pure show <*> pure show'
Prelude Control.Applicative>
Prelude Control.Applicative> :i (<$>)
(<$>) :: Functor f => (a -> b) -> f a -> f b
-- Defined in `Data.Functor'
infixl 4 <$>
Prelude Control.Applicative> :i (<*>)
class Functor f => Applicative f where
...
(<*>) :: f (a -> b) -> f a -> f b
...
-- Defined in `Control.Applicative'
infixl 4 <*>
Prelude Control.Applicative>
```

From the definition of `<$>`

, I would expect `show <$> show <$> Just 3`

to fail, too.